The relationship between service quality perceptions and the level of hospital accreditation - Syahrir A. Pasinringi; Fridawaty Rivai; Nur Arifah; Siti Fatmala Rezeki (Elsevier, 2021)
Background: The quality of health services has long received global attention. Consequently, safe and quality health services in hospitals have become the main hopes and goals of the community, health workers, managers, owners, and regulators. A common external strategy used globally involves recognizing the applied quality management system, specifically certification and accreditation. Objective: Therefore, the purpose of this study is to determine the relationship between levels of quality perception and accreditation in hospitals based on several variables. Methods: A total of 13 hospitals were examined in this cross-sectional study, while a questionnaire consisting of 24 validated items was used for data collection. Subsequently, the analysis was performed by utilizing descriptive statistics and chi-square techniques. Results: From the results obtained, the patient assessment, drug use management, patient and family education, infection prevention and control, alongside facility management and safety variables, had a relationship with the level of hospital accreditation, while patient service did not. Conclusions: Therefore, each hospital is expected to improve its service quality and accreditation.